Ideali e idoli: la creazione della statua divina nella Stele di Neferhotep I da Abido - Colonna, Angelo (Henoch, 2023)
The Stela of Neferhotep i from Abydos offers a unique way of access to ancient Egyptian discourses and practices on the production, manipulation, and mobilisation of the divine statue. The episode of the fabrication of the divine image for the Osiris mysteries sheds light on the complexity and significance of the process, highlighting the interplay of multiple levels (intellectual, material, social, ideological).The paper engages in a focussed analysis of the stela, situating the interpretation of the episode narrated in the theoretical framework of agency, materiality, and relationality of gods as physical objects, and assessing the value of the image as a focal point of conceptualisation, action, and movement within the sacred landscape of Abydos.